If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x^2+2)-9=8x^2+7
We move all terms to the left:
4(3x^2+2)-9-(8x^2+7)=0
We multiply parentheses
12x^2-(8x^2+7)+8-9=0
We get rid of parentheses
12x^2-8x^2-7+8-9=0
We add all the numbers together, and all the variables
4x^2-8=0
a = 4; b = 0; c = -8;
Δ = b2-4ac
Δ = 02-4·4·(-8)
Δ = 128
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{128}=\sqrt{64*2}=\sqrt{64}*\sqrt{2}=8\sqrt{2}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-8\sqrt{2}}{2*4}=\frac{0-8\sqrt{2}}{8} =-\frac{8\sqrt{2}}{8} =-\sqrt{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+8\sqrt{2}}{2*4}=\frac{0+8\sqrt{2}}{8} =\frac{8\sqrt{2}}{8} =\sqrt{2} $
| 80-2x=34x= | | 2p/4=28 | | 5x/2-3=6x+3 | | 2x+33=4(x+3) | | -5x+19=-2x+1 | | 10(30x+2)=70 | | 5x/2-3=6(x+1/2) | | (e/5)-4=-3 | | 2(x-3)^2-10=22 | | n/2-1/3=1/6 | | 2a+3=3a-1 | | 6x + 4 = 9x + 22 | | 7a(-7a)=0 | | a/3+2=13 | | 7m+4=73 | | 3×(2+3)=x | | x+31+x+20+x=180 | | 10x+3=12x-17 | | 73/4-x=11/2 | | x-0.15=1/4 | | 120+120+120+110+x+(x+10)=720 | | 6n+4=4 | | 82+2x=94+x | | (5x-2)^2/x-3=4-20x+25x^2/24-11x+x^2 | | 6m^2-m-22=0 | | 3y+5=44=13 | | H=3+14t-5t2 | | 9×3^3x+4=9^x | | 3a+2=a-7 | | (-3/2)^12=(-9/16)-2x | | 7+8x=52x+31 | | 7+8x=52+31 |